Professor Halina Janaszek-Ivaničková as an Advocate of Modern Comparative Studies During Hopeless, Hard and Critical Times - Zieliński, Bogusław (Poznańskie Studia Slawistyczne, 2018)
Scientific work of Professor Halina Janaszek-Ivaničková (1931–2016) can be placed in three postwar periods of Poland’s history, albeit her scientific and organizational work with regard to comparative studies was carried out on a few continents. Her scientific programme, methodological inspirations and message in each of those periods were aimed against regime limitations, but simultaneously pointed to a positive programme suggesting what can be done and what is right. Initially her programme could be placed with positivistic message and Bakhtin methodology (studies on Stefan Żeromski and Karol Čapek), only for the first lady of Polish comparative studies to become after a breakthrough Revolutions of 1989 a promotor of postmodernism in Poland and other Slavic countries (“From modernism to postmodernism”, 1996). Later she pointed to a “change of paradigm” and foresaw the decline of postmodern formation (“New face of postmodernism”, 2002). With a sharp mind she anticipated a radical “turn to the right” which we are now witnessing. In her last years she was working on a monography on Warsaw Uprising (1 August – 3 October 1944) during which her father, colonel Jan Wacław Janaszek, a soldier of antifascism Home Army, died.